Isolation of Pathogenic Bacteria from Equipment of the Care Units, Hands and Mobile Devices for Medical Staff in Educational Al-Hussein Hospital - Amany Shakeir Jaber, Hussein Ahmed Juma, Ali Abdul Karim Aliwi (Pakistan Journal of Medical & Health Sciences, 2023)
Bacterial contamination of intensive care units is of medical concern because it is one of the large risk factors of ICU -acquired infections and centre point of multi-drug resistant pathogens . Cell phones are important source of the microbial transmission as human pathogens also may be cause increased risk for incidence of bacterial infections as well as natural microbiota of human skin .The aim of this study to isolate and diagnose bacteria from intensive care units and mobile devices for medical staff in these units at Educational Al -Hussein Hospital In the city of Nasiriyah. Collection of samples from teaching Al-Hussein hospital, the number of samples 100 distributed Between Swabs of mobiles(30) teaching Al-Hussein hospital medical staffs and ( 50) from hands of nursing and worker and Technicians and doctor Stethoscope also collecting samples(20) swab from department of ICU (Intensive care unit),CCU (Critical care unit), RCU (Respiratory care unit) collect the samples from medical equipment in care unit (ECG (Electro cardio graph), DC- Shock, Suction Device (sucker) , Monitor Device and Ventilator Device )analyzed by standard Bacteriological methods. The frequency pathogenic bacteria obtained in clinical isolates from the sections was 60 out of 20 swab. The maximum frequency of E. coli is 15 isolates by (25)%, most of them in Ventilator Device, The lowest frequency was for Staphylococcus epidermitis with 3 isolates by (5)%, mostly in Suction unit(sucker)and The positive culture was (32) which is more than negative culture(18) out of 50 swabs, But higher positive culture found in a stethoscope with 8 isolates (25)% followed by in hands of technician , Workers , with 7 isolates (21.8)% Respectively as well as highest number and percentage of bacterial contaminated on phone of medical and health staffs were E.coli, Enterococcus faecalis(16.3 ) % Respectively followed by Staphylococci aureus (14.5%), and Klebsiella pneumonia (12.7%) .bacterial cultures found at higher rate among age groups (31-40) years by 56.3%. But the female showed higher rate of bacterial cultures compares to males by 56.2% . Keywords: intensive care units( ICU ) , Bacterial contamination , E.coli , Hospital